1987
DOI: 10.1148/radiology.163.2.3562823
|View full text |Cite
|
Sign up to set email alerts
|

Dural fistulas involving the cavernous sinus: results of treatment in 30 patients.

Abstract: Thirty symptomatic indirect carotid cavernous fistulas were treated between 1978 and 1986 with a variety of treatment modalities. Combined carotid artery and jugular vein compression resulted in a complete cure in seven of 23 patients (30%) and improvement in one additional patient. There were no complications from this treatment, which is performed by the patient on an outpatient basis. Patients in whom carotid jugular compression therapy failed or who demonstrated cortical venous drainage or visual decline w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
93
0
12

Year Published

1989
1989
2015
2015

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 215 publications
(106 citation statements)
references
References 0 publications
1
93
0
12
Order By: Relevance
“…Given the benign features of low-flow CS DAVFs and possibility of spontaneous occlusion, some authors have advocated conservative treatments, including cervical carotid artery and jugular vein compressions, as first-line therapies for these lesions. 15,40 However, some cases present with intractable intraocular hypertension or reduced ocular perfusion pressure, thereby warranting more rapid interventions to prevent progressive vision loss. 36,40,49 Due to their unique anatomy and symptomatology, CS DAVFs are often categorized using the Barrow classification system.…”
Section: Comparison Of Cs Davfs and Ncs Davfsmentioning
confidence: 99%
“…Given the benign features of low-flow CS DAVFs and possibility of spontaneous occlusion, some authors have advocated conservative treatments, including cervical carotid artery and jugular vein compressions, as first-line therapies for these lesions. 15,40 However, some cases present with intractable intraocular hypertension or reduced ocular perfusion pressure, thereby warranting more rapid interventions to prevent progressive vision loss. 36,40,49 Due to their unique anatomy and symptomatology, CS DAVFs are often categorized using the Barrow classification system.…”
Section: Comparison Of Cs Davfs and Ncs Davfsmentioning
confidence: 99%
“…6 However, endovascular management of these and other dural arteriovenous fistulas (DAVFs) is both curative and safe. 3,[17][18][19][20][21][22][23][24][25] In the present series, the diagnosis of MSF was complicated by a clinical presentation similar to that of a CCF. Misdiagno-sis on the basis of clinical presentation and/or noninvasive imaging may lead to the inappropriate dismissal of an MSF as a benign indirect CCF.…”
Section: Discussion/resultsmentioning
confidence: 98%
“…Complete regression or improvement of symptoms due to spontaneous thrombosis is reported in 25%-90% of cases. [17][18][19][20] Whereas these reports include all types of cavernous sinus fistula, a previous study on patients with Barrow type B fistulas and without embolization found clinical cure in 69.6% of patients and improvement in 13% of patients. 21 For many years balloon embolization was the criterion standard for the treatment of direct AVF of the cavernous sinus.…”
Section: Discussionmentioning
confidence: 99%